Improved physicochemical and functional properties of dietary fiber from Rosa roxburghii pomace fermented by Bacillus natto. (December 2022) - Wang, Yan-Qiu; Wang, Jian-Dong; Cai, Zi-Hui; Huang, Han; Zhang, Su; Fu, Li-Na; Zhao, Peng-Quan; Yan, Xin-Yu; Fu, Yu-Jie
Abstract: Rosa roxburghii juice is of increasing importance in recent years and has become a favorite fruit juice in the market due to its extremely high Vc content. Meanwhile, a large amount of pomace from juice process is usually treated as waste. However, the pomace still contains a lot of nutrients and has great reuse value. In this study, the Rosa roxburghii pomace was fermented with Bacillus natto to develop a new healthy food ingredient rich in high quality dietary fiber (soluble dietary fiber, SDF).Under the optimal fermentation process conditions (inoculum concentration 4%, temperature 38.7 °C, time 12 h, and pH 4.97), SDF content of R. roxburghii pomace increased from 7.68% to 10.68%. SEM and FTIR analysis revealed that the fermentation can lead to degradation of cellulose and hemicellulose, resulting in the formation of more porous lax structure, the related functions such as water holding, oil holding, substance adsorption and cation exchange capacity were obviously increased. In addition, 19 phytochemicals from R. roxburghii pomace were quantified by UPLC-QqQ-MS/MS, which demonstrated the fruit pomace also could be used as a functional ingredient in food field. Highlights: The application of healthy and beneficial Bacillus natto helps to produce high-quality dietary fiber from Rosa roxburghii pomace. The fermentation of Bacillus natto enhanced the physicochemical and functional properties of the dietary fiber from Rosa roxburghii pomace. This green fermentation process can improve the utilization and production value of Rosa roxburghii pomace resources.